(untitled) (Annals of Medical Research, 2022)
Aim: To predict the presence of COVID-19 by readily available hematological and biochemical tests. Materials and Methods: A total of 58 children with signs indicative of COVID-19 (28 PCR positive for SARS-CoV2 and 30 negative) were included in this retrospective study. Clinical and laboratory parameters were compared between the groups. Results: White blood cell counts, RDW, MPV, NLR, PLR, LDH and CRP values were found to be higher in pediatric patients with positive PCR tests than children with negative PCR tests (p<0.05). There was a significantly positive correlation between CRP and NLR (r=.566, p<0.001), CRP and PLR (r=.462, p<0.001). Conclusion: CRP, NLR and PLR, which are frequently used as inflammation markers, can help predict PCR positivity for SARS-CoV2. These easy-to-use, tests can guide diagnosis in countries where access to PCR tests is limited.